Benchmarking Madagascar’s Free Zone Competitiveness - World Bank (World Bank, Washington, DC, 2020)
The Government of Mauritius is implementing the Mauritius Africa Strategy, which is focused on positioning Mauritius as a bridge for investment and trade in order to open new markets in Sub-Saharan Africa (SSA). A cornerstone of this strategy is sharing the successful experience of Mauritius in providing an attractive business environment bundled with good infrastructure and services in order to accelerate investments in trade, services and manufacturing in SSA countries. This technical note is in response to a request from both the MAF and Government of Mauritius and the EDBM and GoM for: i) an update of the current status of the SEZ regime in Madagascar i.e. policy, legal, regulatory and institutional framework and current proposals being considered by the GoM as well as opportunities for improvement, ii) benchmarking Madagascar’s main competitors in the global textile and apparel markets (such as Bangladesh, Ethiopia and Kenya) and comparing their SEZ regimes for textile and garment zones to identify competitiveness strengths and weaknesses and lessons learned, and iii) outline opportunities for successful development of the proposed zone for consideration by both the GoM and the MAF and Government of Mauritius.